Enteroaggregative Escherichia coli as etiological agent of endemic diarrhea in Spain: A prospective multicenter prevalence study with molecular characterization of isolates - Llorente, María Teresa; Escudero, Raquel; Ramiro, Raquel; Remacha, María Antonia; Martínez-Ruiz, Rocío; Galán-Sánchez, Fátima; de Frutos, Mónica; Elía, Matilde; Onrubia, Isabel; Sánchez, Sergio (Frontiers in Microbiology, 2023)
Background: Enteroaggregative Escherichia coli (EAEC) is increasingly associated with domestically acquired diarrheal episodes in high-income countries, particularly among children. However, its specific role in endemic diarrhea in this setting remains under-recognized and information on molecular characteristics of such EAEC strains is limited. We aimed to investigate the occurrence of EAEC in patients with non-travel related diarrhea in Spain and molecularly characterize EAEC strains associated with illness acquired in this high-income setting. Methods: In a prospective multicenter study, stool samples from diarrheal patients with no history of recent travel abroad (n = 1,769) were collected and processed for detection of EAEC and other diarrheagenic E. coli (DEC) pathotypes by PCR. An additional case-control study was conducted among children ≤5 years old. Whole-genome sequences (WGS) of the resulting EAEC isolates were obtained. Results: Detection of DEC in the study population. DEC was detected in 23.2% of patients aged from 0 to 102 years, with EAEC being one of the most prevalent pathotypes (7.8%) and found in significantly more patients ≤5 years old (9.8% vs. 3.4%, p < 0.001). Although not statistically significant, EAEC was more frequent in cases than in controls. WGS-derived characterization of EAEC isolates. Sequence type (ST) 34, ST200, ST40, and ST10 were the predominant STs. O126:H27, O111:H21, and O92:H33 were the predominant serogenotypes. Evidence of a known variant of aggregative adherence fimbriae (AAF) was found in 89.2% of isolates, with AAF/V being the most frequent. Ten per cent of isolates were additionally classified as presumptive extraintestinal pathogenic E. coli (ExPEC), uropathogenic E. coli (UPEC), or both, and belonged to clonal lineages that could be specifically associated with extraintestinal infections. Conclusions: EAEC was the only bacterial enteric pathogen detected in a significant proportion of cases of endemic diarrhea in Spain, especially in children ≤5 years old. In particular, O126:H27-ST200, O111:H21-ST40, and O92:H33-ST34 were the most important subtypes, with all of them infecting both patients and asymptomatic individuals. Apart from this role as an enteric pathogen, a subset of these domestically acquired EAEC strains revealed an additional urinary/systemic pathogenic potential.